Evolution of the Drosophila melanogaster Chromatin Landscape and Its Associated Proteins. - Parey, E.; Crombach, A. (Genome biology and evolution, 2019)
In the nucleus of eukaryotic cells, genomic DNA associates with numerous protein complexes and RNAs, forming the chromatin landscape. Through a genome-wide study of chromatin-associated proteins in Drosophila cells, five major chromatin types were identified as a refinement of the traditional binary division into hetero- and euchromatin. These five types were given color names in reference to the Greek word chroma. They are defined by distinct but overlapping combinations of proteins and differ in biological and biochemical properties, including transcriptional activity, replication timing, and histone modifications. In this work, we assess the evolutionary relationships of chromatin-associated proteins and present an integrated view of the evolution and conservation of the fruit fly Drosophila melanogaster chromatin landscape. We combine homology prediction across a wide range of species with gene age inference methods to determine the origin of each chromatin-associated protein. This provides insight into the evolution of the different chromatin types. Our results indicate that for the euchromatic types, YELLOW and RED, young associated proteins are more specialized than old ones; and for genes found in either chromatin type, intron/exon structure is lineage-specific. Next, we provide evidence that a subset of GREEN-associated proteins is involved in a centromere drive in D. melanogaster. Our results on BLUE chromatin support the hypothesis that the emergence of Polycomb Group proteins is linked to eukaryotic multicellularity. In light of these results, we discuss how the regulatory complexification of chromatin links to the origins of eukaryotic multicellularity.